Questions and answers, 1957 & 1958 - La Mere (Sri Aurobindo Ashram, 1973)
Taped conversations of the Mother with the disciples of Sri Aurobindo Ashram; previously issued in fragmentary form in the Bulletin of Sri Aurobindo International Centre of Education.